The Obligation of the Constitutional Court of Indonesia to Give Consideration in the Process of Dissolution of Societal Organizations - Ahmad Saifulloh, Putra Perdana (Constitutional Review, 2018)
The government efforts to dissolve the societal organizations must be carried out in accordance of stages and processes stipulated in the Law on Societal Organizations. Persuasive efforts must be done first before the imposition of administrative sanctions. Administrative sanctions in the form of warning letters and temporary suspensions of activities need to be done before the Government dissolves the societal organizations after a court decision was obtained from the permanent legal force. The writer considered that the dissolution of societal organizations by the Government was urgent for the present, but the Government before dissolving societal organizations should seek consideration from the Constitutional Court of Indonesia as the guardian, and interpreter of Pancasila. Thus, the Constitutional Court of Indonesia as a neutral judicial institution shall have the authority to consider whether a societal organization will be dissolved.